The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.neuropsychologia.2021.108052
|View full text |Cite
|
Sign up to set email alerts
|

Impaired emotion perception and categorization in semantic aphasia

Abstract: According to a constructionist model of emotion, conceptual knowledge plays a foundational role in emotion perception; reduced availability of relevant conceptual knowledge should therefore impair emotion perception. Conceptual deficits can follow both degradation of semantic knowledge (e.g., semantic 'storage' deficits in semantic dementia) and deregulation of retrieval (e.g., semantic 'access' deficits in semantic aphasia). While emotion recognition deficits are known to accompany degraded conceptual knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 81 publications
(135 reference statements)
2
10
0
Order By: Relevance
“…This is consistent with theory that perception of discrete emotions relies on semantic knowledge (Lindquist et al, 2015). Indeed, perception of emotion categories is impaired following deficits in semantic storage (Lindquist et al, 2014) and semantic control (Souter, Lindquist, & Jefferies, 2021). Matching words by valence may require participants to focus on a specific feature of a concept while disregarding others that together determine global similarity.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This is consistent with theory that perception of discrete emotions relies on semantic knowledge (Lindquist et al, 2015). Indeed, perception of emotion categories is impaired following deficits in semantic storage (Lindquist et al, 2014) and semantic control (Souter, Lindquist, & Jefferies, 2021). Matching words by valence may require participants to focus on a specific feature of a concept while disregarding others that together determine global similarity.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, facial emotions can cue appropriate interpretation of ambiguous words that have both positive and negative meanings in SA (Lanzoni et al, 2019), suggesting that emotional features can modulate semantic control demands by constraining retrieval. SA patients also show some deficits in accessing emotions from facial portrayals; common control processes may constrain the retrieval of both meaning and emotion (Souter, Lindquist, & Jefferies, 2021).…”
mentioning
confidence: 99%
“…A preliminary investigation demonstrated that gamification may facilitate the rehabilitation of word production following stroke (Romani et al, 2019). The current findings extend this study to show that SA patients can benefit from this strategy, despite deficits of semantic control being accompanied by difficulties in constraining internal representational states in domains beyond semantic cognition, including emotion perception (Souter, Lindquist, et al, 2021) and episodic memory (Stampacchia et al, 2018). These findings merit further investigation of the use of gamified extrinsic incentives in addressing post‐stroke impairments in semantic control.…”
Section: Discussionsupporting
confidence: 72%
“…Given this distinction, there is a need to investigate the effects of motivation in tasks with high semantic control demands to establish if this domain can benefit from 'gamification' strategies to the same degree as other cognitive tasks. Furthermore, evidence suggests affective abnormalities in SA, including the ability to categorise facial portrayals according to discrete emotion categories (Souter, Lindquist, & Jefferies, 2021). This is thought to reflect deficits in constraining internal states beyond the conceptual domain, which may extend to and, therefore, limit modulatory effects of motivation.…”
mentioning
confidence: 99%
“…It may be that impaired semantic control does not necessitate executive impairment (Chapman et al, 2020), but that the proximity of these substrates means that these functions are frequently impaired together. Frequent damage to substrates underlying semantic or domain-general control or both in SA may give rise to broad deficits in constraining internal aspects of cognition (Souter et al, 2021; Stampacchia et al, 2018), reflected in heightened susceptibility to external cues and miscues in semantic retrieval (Jefferies et al, 2008; Noonan et al, 2010), along with strong effects of distractors in semantic decision-making (Corbett et al, 2011; Noonan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%